Understanding primary school english teachers' responses about class size to students' achievement in Pengerang Zone, Kota Tinggi District, Johor / Ambiga Sugunabalan and Aminahbibi Saidalvi - Sugunabalan, Ambiga; Saidalvi, Aminabibi (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
The debate over class sizes has been intense over the past decades in the field of education. Therefore, this study aimed to gain an understanding of the scenario of teaching different class sizes from the perspectives of the teachers, in particular relating to students' achievement in English subject. The purpose of this study is to gather and understand teachers' responses concerning class size to students' achievement, particularly English Language teachers in primary schools. This study is significant as it has highlighted teachers' agreement on smaller classes increasing students' academic performance. The findings of this study were gathered through means of questionnaire involving 37 primary school English teachers in Pengerang zone, Kota Tinggi district, Johor. The quantitative data from the questionnaire was analysed using GNU PSPP Statistical Analysis Software for the descriptive analysis. The findings of this study revealed that all the 37 participants agreed that smaller class sizes increase students' achievement in English Language; hence they agreed the significance of class sizes related to academic performance. Moreover, several issues associated with large classes are discussed from the English teachers' perspectives.